Lgr4 in Ocular Development and Glaucoma - Stefan Siwko; Li Lai; Jinsheng Weng; Mingyao Liu (Journal of Ophthalmology)
The leucine-rich repeat-containing G protein-coupled receptor 4 (LGR4, also called GPR48) plays a key role in multiple developmental processes, and mice lacking Lgr4 display anterior segment dysgenesis leading to early-onset glaucomatous retinal ganglion cell loss as well as defective eyelid formation. This paper will review Lgr4 signaling and its regulation of the Axenfeld-Rieger syndrome gene Pitx2, a crucial developmental transcription factor. In addition, Wnt signaling plays an important role in eye development, with Norrin functioning to activate the Wnt receptor Frizzled 4 required for proper retinal vascularization. Recent discoveries identifying Lgr4 as a receptor for Norrin highlight the potential for Lgr4 function in retinal vascularization. Finally, several unanswered questions impeding a full understanding of Lgr4 in glaucoma are considered as avenues for further research.